2018
DOI: 10.3389/fmicb.2018.02989
|View full text |Cite
|
Sign up to set email alerts
|

Clonal Spread of Escherichia coli ST93 Carrying mcr-1-Harboring IncN1-IncHI2/ST3 Plasmid Among Companion Animals, China

Abstract: The purpose of this study was to investigate the occurrence of plasmid-mediated colistin resistance gene mcr-1 in Enterobacteriaceae isolates from companion animals in Guangzhou, China. Enterobacteriaceae isolated from 180 samples collected from cats and dogs were screened for mcr-1 by PCR and sequencing. MCR-1-producing isolates were further characterized by multilocus sequence typing and pulsed-field gel electrophoresis (PFGE). Plasmid characterization was performed by conjugation, replicon typing, S1-PFGE, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 33 publications
(46 reference statements)
3
28
0
1
Order By: Relevance
“…PCR and sequencing analysis identified the mcr-1 gene in one of the colistin-resistant isolates. The mcr-1 prevalence in E. coli isolates in this study was lower than those previously reported in E. coli recovered from companion animals in Argentina (1.9%) [25], Beijing, China (2.3%) [27], and Guangzhou, China (6.25%) [28]. However, it was almost similar to our previously described mcr-1 detection in food animals in Korea [12].…”
Section: Resultssupporting
confidence: 77%
“…PCR and sequencing analysis identified the mcr-1 gene in one of the colistin-resistant isolates. The mcr-1 prevalence in E. coli isolates in this study was lower than those previously reported in E. coli recovered from companion animals in Argentina (1.9%) [25], Beijing, China (2.3%) [27], and Guangzhou, China (6.25%) [28]. However, it was almost similar to our previously described mcr-1 detection in food animals in Korea [12].…”
Section: Resultssupporting
confidence: 77%
“…E. coli ST93 were reported in wild birds in Pakistan, associated with the carriage of bla CTX-M-15 [ 28 ]; in beef, veal, pork and poultry, associated with bla CTX-M-1 in Switzerland [ 28 ]; and in broiler chickens carrying bla CTX-M-2 in Brazil [ 39 ]. In addition, ST93 was also associated to the spread of the mcr -1 gene in companion animals and retail food in China [ 40 , 41 ]. Regarding infections in humans, mcr -1-carrying ST93 E. coli was recovered from a patient with bacteremia in Uruguay [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, levels of colistin resistance are consistently low. The gene mcr-1 has also been identified in bacteria from sheep (Tang et al, 2019), poultry (ducks, geese, and pigeons) (Zhang et al, 2018;Zhuge et al, 2019), companion animals (dogs and cats) (Sun et al, 2016;Zhang et al, 2016;Lei et al, 2017;Wang et al, 2018a;Ortega-Paredes et al, 2019;Rumi et al, 2019), and even wild animals (Liakopoulos et al, 2016;Mohsin et al, 2016;Ruzauskas and Vaskeviciute, 2016;Unger et al, 2017;Bachiri et al, 2018;Oteo et al, 2018) (Table 1 and Supporting Information Table S1). The first report of a wild animal carrying mcr-1 gene could be traced back to 2012, when Liakopoulos et al identified five mcr-1-positive E. coli from Larus dominicanus (n = 50) in Argentina, and all mcr-1 genes were located on IncI2 plasmids (Liakopoulos et al, 2016).…”
Section: Prevalence Of Mcr Genes In Animals and Animalderived Food Prmentioning
confidence: 99%